PENGARUH MOTIVASI BELAJAR DAN CARA BELAJAR TERHADAP HASIL BELAJAR IPS TERPADU - Ayu Imelda Viguna; Nurdin Nurdin; Darwin Bangun (FKIP Unila, 2013)
Education is one important component in the development of a nation, because it is through this education can be produced generations of intelligent and skilled as one of the capital to get change for the better repaired. It is not independent of the various factors that affect the learning process in the classroom, such as learning motivation and learning. The purpose of this study was to determine the effect of motivation to learn and how to learn the result of IPS Integrated learning class VII semester SMP Negeri 1 Way Lima Year Study 2012/2013. Populsi in this study were students of class VII semester SMP Negeri 1 Way Lima by 4 classes with overall student numbers 122 people. By using the formula T. Yamane with probability sampling using simple random sampling obtained a sample of 93 people. The method used in this research is descriptive verification with ex post facto approach and survey issues in this study is whether there is the influence of motivation to learn and how to learn the result of IPS Terpadu learning class VII semester SMP Negeri 1 Way Lima Year Study 2012 / 2013.Based on the analysis of the results obtained show that, (1) There is the influence of motivation on learning outcomes IPS Terpadu VII semester grade students of SMP Negeri 1 Way Lima Year Study 2012/2013, (2) There is the influence of learning styles on student learning outcomes IPS Terpadu class VII semester SMP Negeri 1 way Lima Year study 2012/2013, (3) There is the influence of motivation to learn and how to learn the result of IPS Terpadu learning class VII semester SMP Negeri 1 Way Lima Year study 2012/2013. Keywords: Motivation, Learning Method